Pengaruh Persepsi Dukungan Sosial yang Dirasakan terhadap Mindful Parenting: Model Mediasi Rasa Syukur - Fina Hidayati; Elok Faiz Fatma El Fahmi; Nurul Hartini; Achmad Chusairi (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Early childhood care has such a major implication for individual development that it requires full attention. The present study aimed to determine the effect of perceived social support on mindful parenting mediated by gratitude. This quantitative correlational study involved 232 Indonesian mothers who were recruited randomly to fill the MIPQ, GQ-6, and ISEL-12 questionnaires. Path analysis was conducted using the R software. The results showed that gratitude mediated the relationship between perceived social support and mindful parenting. The mediating role was supported by the bootstrap analysis of the indirect effect (0.12, 95% CI [0.09, 0.16]). Additionally, perceived social support was found to have a significant direct effect on mothers’ gratitude, with a standardized coefficient of 0.23 (p = .000). The finding of this study suggests that positive emotions towards every situation faced by mothers through gratitude enables mothers to practice mindful parenting, characterized by greater awareness and acceptance of their children’s uniqueness. Therefore, it is important to increase a mother’s sense of gratitude, through practical support from their partner and family.